AKTIVITAS ANTIBAKTERI DAN ANTIBIOFILM DARI EKSTRAK DAUN BANGUN-BANGUN (Coleus amboinicus L.) TERHADAP BAKTERI Staphylococcus aureus - Fitra, Romadhonsyah; Romadhonsyah, Fitra; Aisha Nanda Caela Amry; Annisa Fitria; Arde Toga Nugraha; Arba Pramundita Ramadani; Nangim Khasanah (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
Biofilm formation by bacteria, especially the genus Staphylococcus, is a serious health problem. Various medicinal plants have been used to control the infection, but research related to the antibiofilm activity of Coleus amboinicus is still limited. Bangun-bangun leaves (C. amboinicus) are plants from the Lamiaceae family that contain secondary metabolites such as terpenoids, flavonoids, and phenolics that are thought to be responsible as antibacterial and antibiofilm. This study aims to examine the antibacterial and antibiofilm activity of C. amboinicus against S. aureus. C. amboinicus leaves were extracted using 96% ethanol. The ethanol extract was then screened for phytochemicals using Thin Layer Chromatography (TLC) using several spray reagents. Antibacterial activity was analyzed using microdilution technique to obtain the value of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Antibiofilm activity was analyzed using crystal violet method. The result showed that the ethanol extract of C. amboinicus leaves contained flavonoids, phenolic terpenoids, and tannins. Antibacterial assays were obtained for the MIC value of 8 mg/mL and MBC of 16 mg/mL. The ethanol extract showed biofilm inhibitory activity with an IC50 value of 2,40 mg/mL. Based on these results, C. amboinicus has potential antibacterial and antibiofilm activity to inhibit S. aureus.